2021
DOI: 10.1021/acscatal.0c05557
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Coupling of Aryl Chlorides with Aryl Boron Esters Activated by Alkoxides

Abstract: The cobalt-catalyzed Suzuki biaryl cross-coupling of aryl chloride substrates with aryl boron reagents, activated with more commonly used bases, remained a significant unmet challenge in the race to replace platinum group metal catalysts with Earth-abundant metal alternatives. We now show that this highly desirable process can be realized using alkoxide bases, provided the right counterion is employed, strict stoichiometric control of the base is maintained with respect to the aryl boron reagent, and the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…The observed first order in metal catalyst suggests that only one palladium center is involved in the rate‐determining transition state in the model reaction [43] . The 0.7 order in aldehyde ( 1 ) and 0.9 order in olefin (acrylic acid cyclohexyl ester) indicate their pivotal roles either in the rate‐determining step or an equilibrium before this step [44] . The noninteger orders indicate a complex rate law for this reaction [45] .…”
Section: Resultsmentioning
confidence: 94%
“…The observed first order in metal catalyst suggests that only one palladium center is involved in the rate‐determining transition state in the model reaction [43] . The 0.7 order in aldehyde ( 1 ) and 0.9 order in olefin (acrylic acid cyclohexyl ester) indicate their pivotal roles either in the rate‐determining step or an equilibrium before this step [44] . The noninteger orders indicate a complex rate law for this reaction [45] .…”
Section: Resultsmentioning
confidence: 94%
“…In 2021, Bedford and co-workers reported another approach to cobalt−NHC-catalyzed Suzuki cross-coupling of aryl chlorides with aryl boronic esters to access biaryl motifs, where the organoboron nucleophile is activated by alkoxides (Scheme 14). 87 This reaction employs a catalytic amount of CoCl 2 (5 mol %), IPr•HCl (5 mol %), and 1.5 equiv of KO t Bu in THF as a solvent at 60 °C. The comparison between different alkoxide bases in this reaction showed that KO t Bu was superior to its counterparts (K > Na > Li).…”
Section: Cobalt−nhc-catalyzed Cross-coupling Reactionsmentioning
confidence: 99%
“…Examples of cobalt-catalyzed C­(sp 2 )–C­(sp 2 ) cross-coupling with organoboron nucleophiles have been reported using select neutral ligands, including bis­(phosphino)­pyridine pincers, terpyridine chelates, and aryl-substituted N-heterocyclic carbenes (Scheme A). , The understanding of ligand-to-metal complexation has significant implications on the reproducibility of a cross-coupling reaction and demonstrates the inherent difficulty in cross-coupling reaction development. More broadly, understanding catalytically relevant oxidation states, the nature of the active species, and redox cycles in cobalt-catalyzed cross-coupling lags behind iron- and nickel-catalyzed variants. , …”
Section: Introductionmentioning
confidence: 99%